SAT0149 EXPOSURE-RESPONSE RELATIONSHIPS FOR EFFICACY AND SAFETY OF FILGOTINIB AND ITS METABOLITE GS-829845 IN SUBJECTS WITH RHEUMATOID ARTHRITIS BASED ON PHASE 2 AND PHASE 3 STUDIES. (2nd June 2020) - Meng, A.; Anderson, K.; Nelson, C.; Kirby, B.; Ni, L.; Chuang, S. M.; Kearney, B.; Mathias, A.
Abstract : Background: Filgotinib is an orally administered small molecule that provides selective inhibition of JAK1, a signaling molecule that helps drive inflammatory pathways underlying rheumatoid arthritis (RA). Objectives: Exposure-response (ER) analyses were performed for efficacy following completion of Phase 2 studies over a wide range of doses to support evaluation of 200mg and 100 mg once daily in Phase 3 studies. ER analyses were subsequently performed by using Phase 3 efficacy data to support selection of the proposed registrational dose. ER analyses for safety based on pooled Phase 2 and Phase 3 studies were conducted to examine the safety of evaluated doses. Methods: Population PK analyses were conducted to estimate plasma exposures of filgotinib and GS-829845 (major circulating active metabolite of filgotinib) in both Phase 2 (DARWIN 1 and DARWIN 2) and Phase 3 studies (FINCH 1, FINCH 2, and FINCH 3) encompassing a dose range of 25 to 100 mg twice daily and 50 to 200 mg once daily. As both filgotinib and GS-829845 contribute to efficacy via JAK1 inhibition, their exposures were combined into single parameters, AUCeff and Ctau-eff (effective area under the curve and effective concentration at trough, by accounting for relative inhibition potency and molecular weight) in the ER analyses for various efficacy endpoints (e.g ACR20/50/70 responses) at Week 12 and Week 24. The ER analyses for safety endpoints (the 5 most frequent treatment-emergent adverse events [TEAEs] and Grade 3 or 4 laboratory abnormalities, serious TEAEs, and serious infections) were performed separately for filgotinib and GS-829845 exposures to characterize the individual safety profile of each analyte. The 5 evaluated TEAEs were nausea, nasopharyngitis, upper respiratory tract infection, headache, and hypertension; the 5 Grade 3/4 laboratory abnormalities included lymphocytes decrease, glucose increase, phosphate decrease, triacylglycerol lipase increase, and creatine kinase increase. Results: In the ER analyses for efficacy based on Phase 2 studies, high response rates were demonstrated in ACR20/50/70 across all octile groups in subjects with RA receiving filgotinib and the ER supported further evaluation of both 200 mg and 100 mg once daily doses in Phase 3 clinical studies. Similarly, ER relationships based on pooled Phase 3 studies across various endpoints (e.g ACR20/50/70) consistently revealed high response rates across the exposure range for both the filgotinib 200 mg and 100 mg doses. A trend of increasing response with increasing exposure was observed over the exposure range for multiple secondary efficacy endpoints including ACR50 and ACR70 with the effective exposures at filgotinib 200 mg primarily residing on the plateau of the ER curves. Filgotinib was generally well-tolerated with no individual TEAE or Grade 3 or 4 laboratory abnormality > 5% in the filgotinib 200 mg once daily group up to Week 12. No relationships were observed between filgotinib and GS-829845 exposures (AUC0-24 and Cmax) and the most frequent TEAEs, Grade 3/4 laboratory abnormalities, serious TEAEs, or serious infections up to Week 52. Conclusion: ER analyses demonstrate that both the 200 mg and 100 mg once daily filgotinib doses are efficacious in subjects with moderately to severely active RA without clear dose-dependent effects on safety. The trend towards greater efficacy with higher exposures for some secondary endpoints (ACR50 and ACR70) and a lack of exposure-safety relationship supports a dose of 200 mg once daily over 100 mg once daily since it presents the best benefit/risk ratio among the doses tested. Disclosure of Interests: Amy Meng Shareholder of: Gilead Sciences, Employee of: Gilead, Kacey Anderson Shareholder of: Gilead Sciences, Employee of: Sciences, Cara Nelson Shareholder of: Gilead, Employee of: Gilead, Brian Kirby Shareholder of: Gilead, Employee of: Gilead, Liyun Ni Shareholder of: Gilead, Employee of: Gilead, Shu-Min Chuang Shareholder of: Gilead, Employee of: Gilead, Brian Kearney Shareholder of: Gilead, Employee of: Gilead, Anita Mathias Shareholder of: Gilead, Employee of: Gilead